2009
DOI: 10.5483/bmbrep.2009.42.12.834
|View full text |Cite
|
Sign up to set email alerts
|

Putative association of DNA methyltransferase 1 (DNMT1) polymorphisms with clearance of HBV infection

Abstract: DNA methyltransferase (DNMT) 1 is the key enzyme responsible for DNA methylation, which often occurs in CpG islands located near the regulatory regions of genes and affects transcription of specific genes. In this study, we examined the possible association of DNMT1 polymorphisms with HBV clearance and the risk of hepatocellular carcinoma (HCC). Seven common polymorphic sites were selected by considering their allele frequencies, haplotype-tagging status and LDs for genotyping in larger-scale subjects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Moreover, the DNMT1 rs2228611 SNP modified associations between urinary cadmium and hypomethylation of LINE-1 repeated sequences [30]. In addition to these findings, the two intronic polymorphisms rs2241531 and rs4804490 of DNMT1 may be associated with hepatitis B virus (HBV) clearance and protection from the development of hepatocellular carcinoma [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the DNMT1 rs2228611 SNP modified associations between urinary cadmium and hypomethylation of LINE-1 repeated sequences [30]. In addition to these findings, the two intronic polymorphisms rs2241531 and rs4804490 of DNMT1 may be associated with hepatitis B virus (HBV) clearance and protection from the development of hepatocellular carcinoma [31]. …”
Section: Discussionmentioning
confidence: 99%
“…However, some family and twin studies show that host genetic factors are the probable cause influencing the outcome of HBV infection [4,5]. Indeed, our previous studies have demonstrated that genetic variations in histone deacetylase 10, Fas/Fas ligand, transforming growth factor-α/β1, interleukin (IL)10, monocyte chemotactic protein-1, cyclin D2, DNA methyltransferase 1, insulin-like growth factor 2 and secreted phosphoprotein-1 are related to HBV clearance [6,7,8], HCC progression [9,10,11,12], or both [13,14]. In spite of these results, associations of HBV-related liver diseases with other host genetic diversities still need further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…queensu.ca/F-SNP/) (Lee and Shatkay, 2008), DNMT1 rs8101626 on intron 39 of chromosome 19 is predicted to affect the transcriptional regulation of DNMT1 mRNA, whereas DNMT3A rs34048824 on intron 2 of chromosome 2 is predicted to affect the transcriptional regulation of DNMT3A mRNA. Previous studies showed that other intron polymorphisms of DNMT1 + 34542G N C, + 38565G N T, rs10420321 A N G and rs2288349 G N A and DNMNT3A rs11887120 G N A and rs11695471 A N T were associated with disease risk (Kelemen et al, 2008;Chun et al, 2009;Jiang et al, 2012;Tao et al, 2015). Polymorphisms located in introns may affect gene expression by altering mRNA splicing (Moyer et al, 2011), and this could affect cancer susceptibility (Malkinson and You, 1994).…”
Section: Discussionmentioning
confidence: 96%